Fragmentation of Stones by Burst Wave Lithotripsy in the First 19 Humans. Issue 5 (21st May 2022) - Harper, Jonathan D.; Lingeman, James E.; Sweet, Robert M.; Metzler, Ian S.; Sunaryo, Peter L.; Williams, James C.; Maxwell, Adam D.; Thiel, Jeff; Cunitz, Bryan W.; Dunmire, Barbrina; Bailey, Michael R.; Sorensen, Mathew D.
Abstract : Purpose: We report stone comminution in the first 19 human subjects by burst wave lithotripsy (BWL), which is the transcutaneous application of focused, cyclic ultrasound pulses. Materials and Methods: This was a prospective multi-institutional feasibility study recruiting subjects undergoing clinical ureteroscopy (URS) for at least 1 stone ≤12 mm as measured on computerized tomography. During the planned URS, either before or after ureteroscope insertion, BWL was administered with a handheld transducer, and any stone fragmentation and tissue injury were observed. Up to 3 stones per subject were targeted, each for a maximum of 10 minutes. The primary effectiveness outcome was the volume percent comminution of the stone into fragments ≤2 mm. The primary safety outcome was the independent, blinded visual scoring of tissue injury from the URS video. Results: Overall, median stone comminution was 90% (IQR 20, 100) of stone volume with 21 of 23 (91%) stones fragmented. Complete fragmentation (all fragments ≤2 mm) within 10 minutes of BWL occurred in 9 of 23 stones (39%). Of the 6 least comminuted stones, likely causative factors for decreased effectiveness included stones that were larger than the BWL beamwidth, smaller than the BWL wavelength or the introduction of air bubbles from the ureteroscope. Mild reddening of the papilla and hematuria emanating from the papilla were observed ureteroscopically. Conclusions: The first study of BWL in human subjects resulted in a median of 90% comminution of the total stone volume into fragments ≤2 mm within 10 minutes of BWL exposure with only mild tissue injury.